DEVELOPMENT OF CALCIUM-ENRICHED GLUTEN-FREE COOKIES - Quiñones, Renissa S (Journal of Agriculture and Technology Management, 2015)
The increased production of boneless bangus is directly proportional to the volume of discarded spines. Bangus bone meal a by-product of bangus deboning was subjected to laboratory analysis to determine its quality and was used as a functional ingredient in the development of gluten-free cookies for people who are gluten sensitive. The study was laid out in Completely Randomized Design with five treatments in three replications. The experimental samples were subjected to different laboratory procedures using standard methods. Bangus bone meal as functional ingredient for gluten-free cookies affects the physical properties, increased the nutritional status and significant difference (p<0.05) was observed in the flavor and texture sensory attributes as well as consumers’ general acceptability. Bangus bone meal aerobic plate count decreased after three months of storage to ​